2001
DOI: 10.1128/mcb.21.13.4321-4329.2001
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Peroxisomal ATP Carrier Required for Medium-Chain Fatty Acid β-Oxidation and Normal Peroxisome Proliferation in Saccharomyces cerevisiae

Abstract: We have characterized the role of YPR128cp, the orthologue of human PMP34, in fatty acid metabolism and peroxisomal proliferation in Saccharomyces cerevisiae. YPR128cp belongs to the mitochondrial carrier family (MCF) of solute transporters and is localized in the peroxisomal membrane. Disruption of the YPR128c gene results in impaired growth of the yeast with the medium-chain fatty acid (MCFA) laurate as a single carbon source, whereas normal growth was observed with the long-chain fatty acid (LCFA) oleate. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
94
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(101 citation statements)
references
References 57 publications
(61 reference statements)
7
94
0
Order By: Relevance
“…However, more recent works suggest that, in vivo, the membrane is rather impermeable to NAD(H) and acetyl-CoA . ATP for its part has been shown to enter the peroxisomal lumen through the action of a transporter (Palmieri et al 2001), in the absence of which medium-chain (but not long-chain) fatty acids could not be activated into acyl-CoA (Van Roermund et al 2001). …”
Section: Transport To the Peroxisomesmentioning
confidence: 99%
“…However, more recent works suggest that, in vivo, the membrane is rather impermeable to NAD(H) and acetyl-CoA . ATP for its part has been shown to enter the peroxisomal lumen through the action of a transporter (Palmieri et al 2001), in the absence of which medium-chain (but not long-chain) fatty acids could not be activated into acyl-CoA (Van Roermund et al 2001). …”
Section: Transport To the Peroxisomesmentioning
confidence: 99%
“…Previous studies have shown convincingly that Ant1p functions as an Journal of Cell Science 117 (18) ATP carrier in the peroxisomal membrane (Palmieri et al, 2001;van Roermund et al, 2001) and thus links the cytosolic ATP pool to the peroxisomal pool. In ant1∆ cells, we observed a pHper of 7.0 when cells were grown in the medium containing only oleate but also when cells were grown in the medium containing both oleate and glycerol (Tables 1 and 2).…”
Section: Atp Is Necessary To Maintain the Phpermentioning
confidence: 99%
“…Earlier we reported the existence of two independent pathways for fatty acid transport across the peroxisomal membrane (Hettema et al, 1996): one for activated fatty acids, which depends on the peroxisomal ABC transporter proteins Pxa1p and Pxa2p (Shani et al, 1995;Shani and Valle, 1996;Swartzman et al, 1996) that probably act as acyl-CoA ester transporters (Verleur et al, 1997), the other for free fatty acids, which depends on the peroxisomal acyl-CoA synthetase Faa2p and Pex11p (van Roermund et al, 2000). Furthermore, we and others demonstrated the existence of a peroxisomal ATP transporter (Nakagawa et al, 2000;van Roermund et al, 2001;Palmieri et al, 2001).…”
mentioning
confidence: 99%
“…Also, procyclic glycosomes have many more metabolic functions than bloodstream glycosomes, glycolysis playing only a subordinate role, yet the relative amounts of PEX11 and GIM5A/B are similar in the two stages. The results of mutant and metabolic studies in both trypanosomes and yeast indicate that microbodies are impermeable to NAD(P)(H), acetyl CoA, and ATP/ADP (12,40), although a candidate ATP/ADP carrier (unrelated to PEX11) has been found (41). Conversely, the apparent permeability of peroxisomes to solutes such as sucrose does suggest that the membranes may contain a porin; so far the only candidate identified is a 31-kDa protein of unknown sequence from Candida (42).…”
Section: Pex11 Proteins Form a Basis For Assembly Of Membraneassociatmentioning
confidence: 99%